2020
DOI: 10.3390/cells9010195
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1α: The Master Regulator of Endothelial Cell Senescence in Vascular Aging

Abstract: Aging is one of the hottest topics in biomedical research. Advances in research and medicine have helped to preserve human health, leading to an extension of life expectancy. However, the extension of life is an irreversible process that is accompanied by the development of aging-related conditions such as weakness, slower metabolism, and stiffness of vessels. It also debated that aging can be considered an actual disease with aging-derived comorbidities, including cancer or cardiovascular disease. Currently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 150 publications
(242 reference statements)
1
36
0
Order By: Relevance
“…Moreover, since angiogenic cytokines may upregulate vascular endothelial factor (VEGF), whose expression is also directly induced by HIF1α, we additionally examined VEGF, as a peculiar molecule known for its wide-ranging functions, known for its role in angiogenesis and vasculogenesis, to promote vascular development, permeability, and en-dothelial outspreading, but also investigated based on its role as a neurogenic, neurotrophic and neuroprotective factor in the nervous system [65]. To integrate the study of the inflammatory pathway, based on the notion that hypoxia-inducible factors (HIFs) play as essential regulators of inflammation [62,63], we investigated the expression of HIF1α, which is regulated at protein level in an oxygen-sensitive manner, and is known as a critical transcription factor with an essential role in aging-related pathology [64]. Moreover, since angiogenic cytokines may upregulate vascular endothelial factor (VEGF), whose expression is also directly induced by HIF1α, we additionally examined VEGF, as a peculiar molecule known for its wide-ranging functions, known for its role in angiogenesis and vasculogenesis, to promote vascular development, permeability, and endothelial outspreading, but also investigated based on its role as a neurogenic, neurotrophic and neuroprotective factor in the nervous system [65].…”
Section: Inflammatory Pathway (Il6 Gfap) and Hif1α Assessmentmentioning
confidence: 99%
“…Moreover, since angiogenic cytokines may upregulate vascular endothelial factor (VEGF), whose expression is also directly induced by HIF1α, we additionally examined VEGF, as a peculiar molecule known for its wide-ranging functions, known for its role in angiogenesis and vasculogenesis, to promote vascular development, permeability, and en-dothelial outspreading, but also investigated based on its role as a neurogenic, neurotrophic and neuroprotective factor in the nervous system [65]. To integrate the study of the inflammatory pathway, based on the notion that hypoxia-inducible factors (HIFs) play as essential regulators of inflammation [62,63], we investigated the expression of HIF1α, which is regulated at protein level in an oxygen-sensitive manner, and is known as a critical transcription factor with an essential role in aging-related pathology [64]. Moreover, since angiogenic cytokines may upregulate vascular endothelial factor (VEGF), whose expression is also directly induced by HIF1α, we additionally examined VEGF, as a peculiar molecule known for its wide-ranging functions, known for its role in angiogenesis and vasculogenesis, to promote vascular development, permeability, and endothelial outspreading, but also investigated based on its role as a neurogenic, neurotrophic and neuroprotective factor in the nervous system [65].…”
Section: Inflammatory Pathway (Il6 Gfap) and Hif1α Assessmentmentioning
confidence: 99%
“…It is also shown that SIRT1 is necessary for stabilizing HIF-1α [24]. Interestingly, a mechanistic link has been suggested between these molecules (SIRT1, HIF-1α, and eNOS) [23,24,[41][42][43][44], although the role of SIRT1 on anesthetic conditioning-induced DCI protection in SAH has yet to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, HIF-1α is associated with bone resorption in microenvironmental hypoxia [ 17 ] and increases with ischemic osteonecrosis [ 31 ]. In addition, activation of HIF1-α induces senescence-associated secretory phenotypes (phenomenon in which senescent cells express and secrete a variety of inflammatory proteins into their surroundings) and increases the expression of pro-inflammatory cytokines [ 32 ]. In the present study, the CP group showed a significant increase in HIF-1α expression in comparison with the Control and LP groups.…”
Section: Discussionmentioning
confidence: 99%